Metabolic consequences of feeding frequency in man - Wadhwa, P.Sudha; Young, Eleanor A.; Schmidt, Kathryn; Elson, Charles E.; Pringle, Dorothy J. (The American journal of clinical nutrition, 1973)
Normal male subjects adapted to a meal- eating pattern for 4 weeks with caloric intake limited to two meals, 1/8 at 8:00 am and 7/8 at 5:00 pm (gorgers), exhibited abnormal insulin responses to 100-g oral glucose loads. Insulogenic indices were abnormally high 2 hr after a glucose load in these subjects. These subjects then consumed isocaloric diets in eight equal meals (nibblers) during the hours of 8:00 am to 10:00 pm. Both insulin responses and insulogenic indices were returned to normal within 1 week and after 4 weeks values were below pretest levels. In these studies, corn oil (CO) was the major fat source. In a subsequent study, butter oil (BO) was used in place of CO to determine the effect of the dietary fat on carbohydrate and lipid metabolism. At fasting, CO subjects had higher serum triglyceride levels, whereas BO subjects had higher serum cholesterol, free fatty acids and total lipids, and higher blood glucose levels. Phospholipids were not affected by the diets. In the gorging subjects blood glucose levels were higher. Following oral glucose loads, serum triglycerides increased sharply in subjects adapted to CO gorging; in CO nibblers, the triglyceride response was considerably dampened. The feeding pattern did not influence the serum triglyceride of BO subjects following oral glucose loading. Also, blood glucose levels were not greatly affected by the feeding pattern in these subjects, whereas in CO subjects, gorging caused a striking increase. It may be important that blood glucose levels of both BO gorgers and nibblers resembled that of CO gorgers.